Foundations of re-enchantment: Freemasonry, Theosophy, and the occult revival - Coome, Christopher (Oxford studies in Western esoterism, 2025)
"The Foundations of Re-Enchantment provides an exploration of mystical and occult organizations that blossomed at the turn of the 19th century. The four most influential of these movements were the Theosophical Society, the Hermetic Order of the Golden Dawn, the Ordo Templi Orientis, and the Anthroposophical Society. While generally heterodox, these organizations were engaged in the most pressing scientific, religious, and cultural questions of the day, and the occultists applied their insights to fields as diverse as gender norms, interfaith relations, and epistemology. Scholars often view this occult moment as highly innovative-which it certainly was-but it was also deeply in debt to another movement: Freemasonry. Examining why that was the case, and why the occultists were so dependent on Freemasonry reveals a long running current of religious innovation and experimentation that has yet to receive significant scholarly attention"-- Provided by publisher